Sub-lethal glyphosate exposure alters flowering phenology and causes transient male-sterility in Brassica spp - Londo, Jason; McKinney, John; Schwartz, Matthew; Bollman, Mike; Sagers, Cynthia; Watrud, Lidia (BMC plant biology, 2014)
Herbicide resistance in weedy plant populations can develop through different mechanisms such as gene flow of herbicide resistance transgenes from crop species into compatible weedy species or by natural evolution of herbicide resistance or tolerance following selection pressure. Results from our previous studies suggest that sub-lethal levels of the herbicide glyphosate can alter the pattern of gene flow between glyphosate resistant Canola®, Brassica napus, and glyphosate sensitive varieties of B. napus and B. rapa. The objectives of this study were to examine the phenological and developmental changes that occur in Brassica crop and weed species following sub-lethal doses of the herbicides glyphosate and glufosinate. We examined several vegetative and reproductive traits of potted plants under greenhouse conditions, treated with sub-lethal herbicide sprays. Our results indicate that exposure of Brassica spp. to a sub-lethal dose of glyphosate results in altering flowering phenology and reproductive function. Flowering of all sensitive species was significantly delayed and reproductive function, specifically male fertility, was suppressed. Higher dosage levels typically contributed to an increase in the magnitude of phenotypic changes. These results demonstrate that Brassica spp. plants that are exposed to sub-lethal doses of glyphosate could be subject to very different pollination patterns and an altered pattern of gene flow that would result from changes in the overlap of flowering phenology between species. Implications include the potential for increased glyphosate resistance evolution and spread in weedy communities exposed to sub-lethal glyphosate.